IMMUNOMODULATORY ACTIVITY OF AQUEOUS EXTRACTS OF ENICOSTEMA AXILLARE LEAVES AND TODDALIA ASIATICA ROOT BARK - BALAJI PANDIYAN,; VENKATACHALAM VENKATACHALAM,; SIVAKKUMAR THILLAINAYAGAM,; KANNAN KAMARAJAN, (International Journal of Pharma and Bio Sciences, 2015)
Aqueous extracts of leaves of Enicostema axillare (200 mg/kg body weight) and root bark of Toddalia asiatica (100 mg/kg body weight) were evaluated for cell mediated and humoral immunity immune response in rats. The parameters studied for cell mediated immune response were delayed type hypersensitivity response, neutrophil adhesion test, carbon clearance test and cyclophosphamide induced myelosuppression whereas, humoral mediated immunity was evaluated by its effect on humoral antibody titer and serum immunoglobulins. Aqueous extracts significantly increased the paw thickness, neutrophil adhesion to nylon fibers, phagocytic index and effective in restoring cyclophosphamide-induced myelosuppression, indicating its effect on overall cell mediated immunity. Similarly both extracts exhibited a significant increased level of circulating antibody titer and serum immunoglobulins suggesting an increase in humoral mediated immunity also. The effects exhibited are comparable to that of levamisole at 50 mg/kg dose level.